2017
DOI: 10.1103/physreve.96.043202
|View full text |Cite
|
Sign up to set email alerts
|

Transport regimes spanning magnetization-coupling phase space

Abstract: The manner in which transport properties vary over the entire parameter-space of coupling and magnetization strength is explored. Four regimes are identified based on the relative size of the gyroradius compared to other fundamental length scales: the collision mean free path, Debye length, distance of closest approach, and interparticle spacing. Molecular dynamics simulations of self-diffusion and temperature anisotropy relaxation spanning the parameter space are found to agree well with the predicted boundar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…The spontaneously generated temperature anisotropy, will relax at a rate that depends on the coupling strength Γ and the magnetic field strength β [10][11][12]. Recent results [27] (for the one component plasma) suggest that for a coupling strength of Γ = 0.1 and magnetic field strength of β = 100, the temperature isotropization time is ∼ 10 6 ω −1 pe . This would be a sufficiently long delay that the electron temperature anisotropy would last for the complete ultracold plasma lifetime, which can last up to 250 µs (or few hundreds of ω −1 pi ).…”
Section: Magnetized Ultracold Plasmamentioning
confidence: 98%
See 1 more Smart Citation
“…The spontaneously generated temperature anisotropy, will relax at a rate that depends on the coupling strength Γ and the magnetic field strength β [10][11][12]. Recent results [27] (for the one component plasma) suggest that for a coupling strength of Γ = 0.1 and magnetic field strength of β = 100, the temperature isotropization time is ∼ 10 6 ω −1 pe . This would be a sufficiently long delay that the electron temperature anisotropy would last for the complete ultracold plasma lifetime, which can last up to 250 µs (or few hundreds of ω −1 pi ).…”
Section: Magnetized Ultracold Plasmamentioning
confidence: 98%
“…Previously, Glinsky et al [8], Dubin et al [10,11] and Ott et al [12] have shown that the long lived temperature anisotropy can be maintained for β > 1 in weakly, moderately and strongly coupled plasmas, respectively. Recently, Baalrud et al has provided the temperature anisotropy relaxation rates ranging from weak to strong coupling strength regime and for magnetic field strength β ranging from 0 to 100 using MD simulations [27]. Based on their data, it is expected that a magnetization strength of β e > ∼ 100 (corresponding to B > ∼ 3200 G) may be sufficient to delay relaxation of the electron temperature anisotropy long enough (∼ 10 6 ω −1 pe ) to make measurements over the duration of a typical experiment (∼ 100µs) [6,18].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant physical parameters include the Debye screening length λ (in particular for Γ 1) and the Larmor radius r L . In the context of transport properties, the classical distance of closest approach, b = Q 2 /(4π 0 k B T ), and the mean free path between collisions, λ mfp , have additionally been used to define magnetization regimes, depending on the ratios of r L and {λ mfp , λ, b, a} [22,34]. Note that, in the strongly coupled regime, Γ 1, the Wigner-Seitz radius a eventually becomes smaller than the distance of closest approach and larger than the Debye screening length.…”
Section: Theorymentioning
confidence: 99%
“…Examples range from ions in warm dense matter [1,2] (solid densities), ultra cold neutral [3] and nonneutral plasmas [4] (mK temperatures), to complex (or dusty) plasmas [5] (highly charged dust particles). Recent experimental advances in the magnetic confinement of ultra cold neutral plasmas [6], high energy density matter [7], and dusty plasmas [8][9][10][11], as well as theoretical efforts concerning, e.g., the stopping power [12][13][14][15] and transport coefficients [16][17][18][19][20][21][22][23][24] demonstrate growing interest in the physics of magnetized strongly correlated plasmas-conditions relevant to the outer layers of neutron stars [25][26][27][28][29], confined antimatter [30,31], or magnetized target fusion [32,33]. In this challenging regime, the familiar theory of Braginskii [34] is no longer applicable, and new theoretical concepts as well as first-principle simulations are required.…”
mentioning
confidence: 99%
“…39,40 However, recent molecular dynamics results have shown trends inconsistent with either prediction at strong magnetization. 32 By accounting for screening via the potential of mean force, and for gyromotion via the 2-body interaction inside the collision sphere, one may address in a self-contained way the combined influence of short and long-range interactions. The Bohr-van Leeuwen theorem ensures that the magnetic field does not influence any statistical property at equilibrium, so the potential of mean force is expected to remain unchanged from that presented above.…”
Section: Comment On Strongly Magnetized Plasmasmentioning
confidence: 99%